Comparison of the Efficacy of Educational Film and Clinical Demonstration for Instruction of Fiber-Reinforced Composite Post Restorations to Dental Students - Hajizadeh, Hila; Izadjoo, Malihe; Akbari, Majid (Journal of Dental School, 2019)
Objective: Different educational tools are now commonly used in universities worldwide such as illustrations, audio and videotapes, etc. This study aimed to compare the efficacy of educational film and clinical demonstration for instruction of Fiber-Reinforced Composite (FRC) post restorations to dental students in Department of Restorative Dentistry. Methods: This interventional study was conducted on 70 fifth year dental students in Mashhad University. Students were divided into two groups. Group 1 students watched live demonstration of a treatment procedure (FRC post restoration) while group 2 watched the educational film of the same procedure. Both groups participated in a post-test. Also, students’ perspectives were sought via a questionnaire. Data were analyzed using SPSS, Student’s t-test and Chi-square test. Results: The mean post-test score of group 2 students (educational film) was greater than that of group 1 students (clinical demonstration) and the difference in this respect between the two groups was statistically significant (p=0.008). Considering the score of 7 as an acceptable score, 44 students gained scores 7 or higher; out of which, 16 were in group 1 (clinical demonstration) and 28 were in group 2 (educational film). The difference in this regard between the two groups was statistically significant (p=0.003). Most students preferred watching the educational film to the crowded clinical demonstration sessions. Conclusion: Watching the educational film yielded greater test scores than the clinical demonstration.